2023
DOI: 10.3389/fimmu.2022.1094132
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of blocking PD-1 pathway on retinal ganglion cells in a mouse model of chronic ocular hypertension

Abstract: PurposeIn this study, we aimed to investigate whether Programmed cell death 1 ligand 1/programmed cell death 1 ligand 2 (PD-L1/PD-L2) double knockout (dKO) has a protective effect on RGCs in a mouse model of chronic ocular hypertension (COHT).MethodsWe used superparamagnetic iron oxide to induce COHT in mice. Apoptosis of retinal ganglion cells (RGCs) and activation of microglia were evaluated using western blotting (WB) and immunofluorescence staining of the mouse retina. In addition, we also conducted transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The observed increase in PD-L1 may suggest its involvement in neuroinflammatory processes within the ocular environment in glaucoma. Notably, Sheng et al demonstrated that blocking both the PD-L1/PD-L2 pathways had a protective effect on RGCs and increased the number of anti-inflammatory M2-activated microglia in a mouse model of chronic ocular hypertension [ 43 ]. This suggests that the observed increase in PD-L1 in our study may be indicative of neuroinflammation in glaucoma patients, potentially offering a new avenue for understanding disease mechanisms or developing therapeutic targets [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in PD-L1 may suggest its involvement in neuroinflammatory processes within the ocular environment in glaucoma. Notably, Sheng et al demonstrated that blocking both the PD-L1/PD-L2 pathways had a protective effect on RGCs and increased the number of anti-inflammatory M2-activated microglia in a mouse model of chronic ocular hypertension [ 43 ]. This suggests that the observed increase in PD-L1 in our study may be indicative of neuroinflammation in glaucoma patients, potentially offering a new avenue for understanding disease mechanisms or developing therapeutic targets [ 44 ].…”
Section: Discussionmentioning
confidence: 99%